(untitled) (Economic and Political Thought, 2012)
The actual crisis in the euro zone results from the inconsistent attitude of the members of the region towards the demands of the economic integration process. Its extension towards the creation of an effectively functioning financial and economic union is immanently connected with the need of a bigger and bigger convergence of the economic policy adopted by the participants of the integration actions, especially in the context of their fiscal and budgetary policy. The lack of political will that made full implementation of such a project possible together with a voluntary policy of accessing the euro zone by the states that did not meet the necessary requirements and criteria neither at the moment of accession nor later, and negligence in their execution led to a deep crisis in the zone as well as the whole European Union. The proposed methods of reforming the situation result from the interests of the two European integration ‘engines’: Germany and France, and they do not create conditions necessary for finding a final solution to the existing problems. On the other hand, Poland’s attitude towards the euro zone crisis is determined by the state and perspectives of our economy, the quality of the domestic political elite and the manner of economic management. Confrontation with the problems of the euro zone crisis in the context of accession is strictly determined by the ability to implement necessary reforms in order to create economic conditions adequate to challenges.